Aplikace anabolických steroidů s vitaminem D v časné fázi léčby polytraumatizovaných pacientů – slepá ulička? - Ječmínková, R; Ječmínek, V; Káňová, M; Vrtková, A; Divák, J; Pleva, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2021)
PURPOSE OF THE STUDY Persistent catabolism is one of the main causes of delayed healing in polytrauma patients. The purpose of this study is to verify the effect of early administration of an anabolic steroid in combination with vitamin D on the process of bone healing in polytrauma patients. MATERIAL AND METHODS In this prospective study, the patients with a serious trauma were divided into two groups (a control group and a treatment group), with the treatment group being treated with nandrolone decanoate, an anabolic steroid in combination with vitamin D. In all the patients, bone metabolism markers and sex hormone levels (men only) were monitored through lab testing for the period of 70 days and the results of both the groups were subsequently compared. RESULTS The study included a total of 64 patients, 32 in the control group and 32 in the treatment group. The differences between the groups in gender (p = 0.387) as well as in the age of patients (p = 0.436) were statistically non-significant. There was a significant difference in the Injury Severity Score (48 in the treatment group as against 41 in the control group, p = 0.022). Even though this difference was statistically significant, it cannot be considered clinically significant since all the patients met the major trauma criteria. No positive effect of this treatment on bone metabolism parameters was established; on the very contrary, the only statistically significant changes were observed in the control group. To be specific, in levels of one of the bone formation markers, bone alkaline phosphatase on Day 7 after the injury (an increased level in the control group; p = 0.002) and in one of the bone resorption markers (bone acid phosphatase) on Day 70 after the injury (an increased level in the treatment group; p = 0.042). In the treatment group, 70 days after the injury a higher 25(OH)vitamin D level (p < 0.001) was reported and starting from Day 7 in men in the treatment group a significantly lower testosterone level and free testosterone level were observed. The level of androgenic hormones dramatically dropped in both the groups during the first days after the trauma, the dynamics of its normalization was faster in patients in the control group than in the treatment group. DISCUSSION The administration of nandrolone decanoate, an anabolic steroid, in combination with vitamin D did not produce the expected effect, i.e. an improvement in bone healing markers in polytrauma patients. One would expect that in polytrauma patients with a bone fracture or fractures during bone healing higher levels of all the markers of bone resorption as well as bone formation will persist. Similar increases in bone metabolism levels, however, were observed also in patients with injuries in other somatic regions. This indicates the importance of bone tissue involvement in the overall response of the organism to polytrauma. A faster normalization of the levels of testosterone, dihydrotestosterone and free testosterone in the control group compared to the treatment group corresponds with the supplemental effect of anabolic steroids and reduced production of these hormones as a feedback to hypothalamic-pituitary-adrenal axis. CONCLUSIONS In the follow-up period, the positive effect of anabolic steroid and vitamin D administration on bone metabolism in polytrauma patients was not confirmed. Key words: polytrauma, anabolic steroids, vitamin D, bone metabolism.
Keywords: systém hypotalamus-hypofýza; vitamin D; Multiple Trauma; systém hypofýza - nadledviny; Nandrolone Decanoate; polytrauma; mužské pohlaví; Anabolic Agents; Pituitary-Adrenal System; lidé; Vitamin D; Male; nandrolon dekanoát; Hypothalamo-Hypophyseal System; Prospective Studies; Humans; prospektivní studie; anabolika